X-ray spectrometry with Peltier-cooled large area avalanche photodiodes - Fernandes, L. M. P. (2004)
Performance characteristics of the response of a Peltier-cooled large-area avalanche photodiode are investigated. Detector gain, energy linearity, energy resolution and minimum detectable energy are studied at different operation temperatures. Detector energy resolution and lowest detectable X-ray energy present a strong improvement as the operation temperature is reduced from 25 to 15 °C and slower improvements are achieved for temperatures below 10 °C.